A comparative exploration of the chaotic characteristics of Chinese and international copper futures prices. (September 2022) - Zheng, Shuxian; Tan, Zhanglu; Xing, Wanli; Zhou, Xuanru; Zhao, Pei; Yin, Xiuqi; Hu, Han
Abstract: This study used a C–C method to reconstruct the phase space of copper prices from January 2002 to December 2021, using Chinese and international copper futures price time series as a sample. It demonstrates the differences in the chaotic characteristics of two copper futures prices through recurrence plots and correlation dimensions. Recurrence complex networks have been employed to quantify the spatial structural similarity between the variables and copper prices, and the main factors influencing the structural changes in copper prices have been analysed by a systematic bifurcation mechanism. The results show that the efficiency of the copper futures market has improved gradually. The level of perfection and efficiency of the Chinese copper futures market is lower than that of the international copper futures market, and the predictability of Chinese copper futures prices is even weaker, which means that the investment in Chinese copper futures is riskier than that in the international copper futures market. Compared to other metal futures, such as aluminium and nickel, copper futures are likely to be a lower risk investment. The US dollar index, the federal funds rate and the price of gold are the main factors influencing changes in the spatial structure of copper prices in China, while political risk, crude oil and gold prices are key to shaping the chaotic character of international copper prices. A tipping point in the chaotic state of copper prices could correspond to the onset of a global financial crisis. This study can help policymakers to understand the market laws underlying prices and thus create robust and well-traded markets by controlling the chaotic characteristic structure of copper prices. In addition, the identification of chaotic state thresholds in Chinese and international copper prices can predict the occurrence of unexpected events such as financial crises, which is important to counteract financial market risks. Highlights: The efficiency of the copper futures market has improved gradually. Higher perfection and efficiency in the international copper futures market. Higher investment risk in Chinese copper futures. Gold prices are key to shaping international and Chinese chaotic copper prices. Copper price chaotic state critical point corresponds to the financial crisis.